Turbine blade vibration literature review - Rieger, Neville (Revista Técnica da Faculdade de Engenharia da de Zulia, 1970)
A comprehensive review of the world literature dealing with vibrations of turbine blades is presented. This review includes studies of single blades using discrete mass matrix methods, distributed mass studies, and finite element investigations. Analyses of bIade groups by these methods are also included. The contents of 114 papers on blade vibrations are each briefly summarized with comments relating to how each publication contributes to the present state of knowledge for this subject.